Quantification of acidic compounds in complex biomass-derived streams. Issue 17 (6th June 2016) - Karp, Eric M.; Nimlos, Claire T.; Deutch, Steve; Salvachúa, Davinia; Cywar, Robin M.; Beckham, Gregg T.
Abstract : A robust sample workup protocol is described that allows quantification of acidic components in complex biomass-derived process streams. This protocol is shown to have application in the field of lignin conversion. Abstract : Biomass-derived streams that contain acidic compounds from the degradation of lignin and polysaccharides ( e.g. black liquor, pyrolysis oil, pyrolytic lignin, etc. ) are chemically complex solutions prone to instability and degradation during analysis, making quantification of compounds within them challenging. Here we present a robust analytical method to quantify acidic compounds in complex biomass-derived mixtures using ion exchange, sample reconstitution in pyridine and derivatization with BSTFA. The procedure is based on an earlier method originally reported for kraft black liquors and, in this work, is applied to identify and quantify a large slate of acidic compounds in corn stover derived alkaline pretreatment liquor (APL) as a function of pretreatment severity. Analysis of the samples is conducted with GCxGC-TOFMS to achieve good resolution of the components within the complex mixture. The results reveal the dominant low molecular weight components and their concentrations as a function of pretreatment severity. Application of this method is also demonstrated in the context of lignin conversion technologies by applying it to track the microbial conversion of an APL substrate. Here too excellent results are achieved, and the appearance and disappearance of compounds is observed in agreement with the known metabolic pathways of two bacteria, indicating the sample integrity was maintained throughout analysis. Finally, it is shown that this method applies more generally to lignin-rich materials by demonstrating its usefulness in analysis of pyrolysis oil and pyrolytic lignin.